Joint implementation in Costa Rica: A case study at the community level - Lindegaard, Klaus (2014)
The policy of joint implementation is emerging as a new strategy for implementing global environmental aims, especially with regard to regulating the climate change process, where emission source and sink countries agree to develop a joint program upon a mixed argument of partnership and cost-effectiveness. Pros and cons have emerged during the development of this system. Costa Rica is the first country, together with Norway, to launch such a program jointly, and Costa Rica is also the first country developing Carbon Tradable Offset bonds to be sold on the world market as a new commodity. It is hoped that this initiative will help the country and its inhabitants to create better living conditions and economic growth; however, this new institutional transformation and international acceptance of this new instrument are only just beginning to develop. This, therefore, provides a very interesting field for research from a distinct perspective. We chose to start searching for positive or negative impacts at the community level. In this sense the paper deals with questions such as: What happens at the community level?; Is it possible to realize joint implementation with positive local, social and economic impacts?; and What are the necessary conditions for this to become successful.